Lithium-Nickel Cobalt Oxides with Spinel Structure Prepared at Low Temperature. Xrd, Xps, and Eis Measurements - Ortiz-Farias, J; Ortiz-Farias, J; Gautier-Zamora, J; Gautier-Zamora, J; Ruiz-Leon, D; Ruiz-Leon, D (2012)
Li, Co and Ni mixed oxides of composition LiNi xCo 2 - xO 4 (x = 0.25, 0.5, 0.75 and 1) were prepared at 280 °C by the Pechini sol-gel method. The Rietveld refinement of the X-ray diffraction data indicated that all the obtained compounds crystallize in the Fd3m space group characteristic of cubic spinel-related oxides. XPS studies on these oxides reveal the presence of Ni 2 +, Ni 3 +, Co 3 + and Co 4 + ions at the surface. The diffusion coefficients of the Li + ion in the oxide lattice, determined by EIS measurements, are larger (10 - 13 cm 2s - 1 ? D ? 10 - 10 cm 2s - 1) than that shown by the non-substituted cobalt-lithium oxide, LiCo 2O 4 (D = 10 - 16 cm 2 s - 1) and present similar values to those of layered oxides of related composition. © 2011 Elsevier B.V. All rights reserved.